1989
DOI: 10.1002/smj.4250100507
|View full text |Cite
|
Sign up to set email alerts
|

A systematic comparative analysis and synthesis of two business‐level strategic typologies

Abstract: Two important business‐level strategic typologies were systematically evaluated, analyzed and compared in this study: Porter'S Overall Cost Leadership, Differentiation, Focus, and ‘Stuck in the Middle’ generic competitive strategies, and Miles and Snow'S Defender, Prospector, Analyzer, and Reactor types of organizational adaptation. On the basis of strategic theory, and following a pilot study, 31 strategic variables were evaluated by judges on a seven‐point maximum‐minimum scale, for each strategy, within its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
0
16

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(188 citation statements)
references
References 30 publications
5
167
0
16
Order By: Relevance
“…There are three main typology frameworks of business strategy which have had a substantial impact on MCSs contingency-based research: strategic pattern of , strategic position of Porter (1980) and strategic mission of Gupta and Govindarajan (1984). Despite the differences in their inward/outward focus, Segev (1989) showed that the typologies of and Porter (1980) are consistent and argues that "it is no longer necessary for researchers to enrich their view of a strategic situation by the separate application of each typology" (Segev 1989, p. 500). This framework will adopt Porter's (1980) whereas cost leaders offer standardised products at low prices while reducing production costs, for example with process innovations (Porter 1980).…”
Section: Contingency Factors: Organisational Characteristicsmentioning
confidence: 99%
“…There are three main typology frameworks of business strategy which have had a substantial impact on MCSs contingency-based research: strategic pattern of , strategic position of Porter (1980) and strategic mission of Gupta and Govindarajan (1984). Despite the differences in their inward/outward focus, Segev (1989) showed that the typologies of and Porter (1980) are consistent and argues that "it is no longer necessary for researchers to enrich their view of a strategic situation by the separate application of each typology" (Segev 1989, p. 500). This framework will adopt Porter's (1980) whereas cost leaders offer standardised products at low prices while reducing production costs, for example with process innovations (Porter 1980).…”
Section: Contingency Factors: Organisational Characteristicsmentioning
confidence: 99%
“…In fact, a differentiation strategy relies on strong marketing abilities, product engineering skills, and creative ideas, which are more closely associated with a strategic orientation. In contrast, cost-focused leadership strategies are related to more defensive and conservative orientations (Miles and Snow, 1978;Segev, 1989), because they emphasize process engineering skills, tight cost controls, and efficient distribution systems (Porter, 1980). These differences among competitive strategies suggest that firms seeking to renew or strengthen themselves by adopting a more strategic orientation should achieve better performance when their managers implement differentiation strategies focused on innovation and creativity (Entrialgo et al, 2001).…”
Section: H4: Higher Levels Of Previous Experience Of the Tmt In Othermentioning
confidence: 99%
“…The fourth dimension of EC advantages includes products/services quality improvement. The quality of a product (or a service) can be defined as the degree of superiority of the product (or the service) as perceived by the customers, compared to those of the competitors (Segev, 1989). The use of EC constitutes a means for a company to offer products and services of better quality.…”
Section: Advantagesmentioning
confidence: 99%